MEDULLARY THYROID CARCINOMA (MTC): A CURRENT REVIEW OF EPIDEMIOLOGY, DIAGNOSIS, AND THERAPY - Szymon Zysiak; Julia Wawerska; Dawid Głaz; Maksymilian Głaz; Natalia Kamińska; Jędrzej Zaguła; Magdalena Stolarczyk; Aleksandra Jagura-Sukiennik; Mateusz Stronczyński; Kacper Wicha (International Journal of Innovative Technologies in Social Science, 2025)
Background: Medullary Thyroid Carcinoma (MTC) is a rare neuroendocrine tumor (1–5% of all thyroid cancers) characterized by disproportionately high mortality (13%), often complicated by advanced-stage diagnosis and early metastasis. This malignancy is uniquely driven by RET proto-oncogene mutations.Aim: This review aims to comprehensively analyze contemporary MTC management strategies, focusing on advancements in precision diagnostics, targeted therapies, and identifying critical challenges related to therapeutic resistance and clinical guideline standardization.Materials and Methods: An extensive synthesis of the current literature, prioritizing comprehensive review articles and meta-analyses published within the last five years, was conducted using multiple electronic databases (PubMed, Scopus).Results: Recent breakthroughs include the highly effective and well-tolerated selective RET inhibitors (selpercatinib, pralsetinib), which offer improved outcomes compared to older multikinase inhibitors (MKIs). Diagnostic modalities are enhanced by advanced functional imaging (e.g. [18F]F-DOPA-PET/CT). Despite improved overall survival, the major clinical hurdle remains acquired drug resistance, mediated by RET kinase domain mutations and activation of bypass signaling pathways (MET, EGFR). Furthermore, substantial variability persists across international guidelines regarding optimal prophylactic surgery timing and criteria for initiating systemic treatment.Conclusion: Future efforts must concentrate on establishing unified, dynamic risk stratification protocols, standardizing advanced imaging utilization, and implementing liquid biopsy (ctDNA) guided sequential therapy to effectively overcome acquired resistance and ensure durable long-term disease control.